HAEMOLYTIC ACTIVITY OF LIVE PHAEOCYSTIS POUCHETII DURING MESOCOSM BLOOMS - Van Rijssel M.; Alderkamp A.-C.; Nejstgaard J.C.; Sazhin A.F.; Verity P.G. (My University, 2007)
Chemical defence is a potential mechanism contributing to the success of Phaeocystis species that repeatedly dominate the phytoplankton in coastal areas. Species within the genus Phaeocystis have long been suspected of imposing negative effects on co-occurring organisms. Recently a number of toxins have been extracted and identified from Phaeocystis samples, but it is not clear if they do enhance the competitive advantage of Phaeocystis species. In the present study the cytotoxic impact of live Phaeocystis pouchetii to human blood cells in close proximity, regardless of the nature of the responsible mechanism, was quantified using a bioassay. Haemolytic activity was measured during blooms of P. pouchetii in mesocosms. These environments were chosen to mimic natural conditions including chemically mediated interactions that could trigger defensive and/or allelopathic responses of Phaeocystis. Haemolytic activity correlated with P. pouchetii numbers and was absent during the preceding diatom bloom. Samples containing live P. pouchetii cells showed the highest activity, while filtered sea water and cell extracts were less haemolytic or without effect. Dose-response curves were linear up to 70% lysis, and haemolysis in samples containing live P. pouchetii cells reached EC50 values comparable to known toxic prymnesiophytes (1.9 * 107 cells l−1). Haemolytic activity was enhanced by increased temperature and light. The results indicate that unprotected and thus presumably vulnerable cells present in a P. pouchetii bloom may lyse within days.
Keywords: ALLELOPATHY; CHEMICAL DEFENCE; PRYMNESIOPHYTE; PUA; PUFA